(untitled) (Pubmet, 2022)
Evaluation of scientific productivity and output can be a challenge, especially for developing countries, as national or regional publications are often poorly covered by the international databases. To address this issue, policymakers adopt new instruments and mechanisms to evaluate local and international publications. A number of countries have developed national and regional indexes such as the Chinese Science Citation Database or SciELO, which started in Brazil, and is now covering most South American national output, Spain, and South Africa. In Armenia, the task to build a platform for the Armenian Science Citation Index (ASCI) has been undertaken by the Center for Scientific Information Analysis and Monitoring of the Institute of Informatics and Automation Problems of the National Academy of Sciences to evaluate the scientific output of Armenian researchers, scientific groups, laboratories, and organizations and help develop Armenian journals. We have provisional arrangements in place and intend to have all local Armenian scientific journals included in ASCI. We also plan to cover the publications of Armenian authors published abroad. Our end goal is to establish cooperation with international open scientific databases and exchange information with them. According to our ongoing research, Armenian scientific journals receive a lot of citations abroad and exchange will highly contribute to further international visibility of Armenian scientific journals. This paper presents the future centralized ASCI platform that will include local and international publications and the tools it will employ to analyse and evaluate institutional output, with a few specific examples. Thanks to the NI4OS project funded by EC Horizon 2020, the platform will provide services to interested researchers based on the FAIR principles and eventually be integrated with international scientific databases.